A population-based study of inter-generational attitudes towards consanguineous marriages in north-eastern Brazil. Issue 5 (13th March 2019) - Lima, Shirley O. A.; Farias, Allysson A.; Albino, Victor A.; Marques-Alves, Yanna K.; Olinda, Ricardo; Santos-Silva, Tais A.; Alves, Leandro U.; Zatz, Mayana; Santos, Silvana
Abstract: The aim of this cross-sectional study was to investigate beliefs, attitudes and reproductive behaviours in relation to consanguinity in a population living in the backlands of north-eastern Brazil. Data were collected by face-to-face interview from 147 high school students aged 13–20 years and from 532 elderly individuals aged 60 years and over from Brejo dos Santos in the state of Paraíba in 2017. The frequency of consanguineous marriage was found to have increased over the generations, being 15.9% in the parents of the elderly participants, 17.1% in the elderly participants themselves and 20.5% in their descendants. Although 258 (50.9%) of the elderly interviewees opposed consanguineous union, 341 (65.3%) would approve of the marriage of their children with relatives. Both the young ( n =108 or 78.3%) and elderly ( n =398 or 80.4%) interviewees believed that consanguineous marriages were no more durable than non-consanguineous marriages ( p =0.578). Additionally, 408 (82.4%) of the elderly individuals and 108 (80.6%) of the students recognized that spouses in consanguineous unions experience conflicts, just like other couples do ( p =0.625). In both groups, the majority of the participants did not believe that consanguinity increased the risk of having children with disabilities. The regression of the two continuous variables 'age' and 'positive attitudes score' showed a significant correlation, suggesting that younger individuals are more susceptible to the influence of cultural factors contributing to consanguinity, such as the opinions of their parents and grandparents. The belief that consanguineous unions are more durable showed a significant difference between elderly individuals in consanguineous and non-consanguineous unions ( p =0.001); the former were 2.42 more likely to believe that marriages between relatives contributes to marriage durability.